The training model development to enhance the graduates’ mental well-being - สกุลทอง ลักษณา; ยุระยาตร์ ภมรพรรณ์; หกสุวรรณ สุทธิพงศ์ (Ratchaphruek Journal, 2018)
ABSTRACT This research aims to study the psychological well-being of students who are at the first year of the academic year 2013. The process of studying the survey elements is conducted in order to analyze the confirmation component to incorporate the elements to design a training model for the development of students’ psychological well-being. Experts provide group discussion for advice and improve the tool before applying the qualified confirmation. The model is derived from the certification model, and tries to use with students. The results show the model used experimental students who participated in the training model to develop psychological well-being in the post-experimental period.